(untitled) (Bioagro, 2026)
The genus Urochloa is characterized by its high dry matter production, adaptation to infertile soils and droughts. The aim of this study was to determine the response to different defoliation intensities of the Mavuno grass hybrid on the dry season. The research was conducted in an experimental area in Gomez Farias, Jalisco, from January 2024 until April 2024. The experimental design was completely randomized in a 4 × 3 factorial arrangement, with four regrowth ages 30, 45, 60 and 90 days (d) and three defoliation intensities (5, 10, and 15 cm) with three replications. The yields of green forage and dry matter (DM), plant height, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), ether extract (EE), ash, organic matter (OM), metabolizable energy (ME) and in situ dry matter digestibility (ISDMD) were determined. The yields of green forage and DM were affected by defoliation intensity and maturity stage (p≤0.01). At 10 cm × 30 d of regrowth interaction a high CP (16.57 %) and low ADL (3.44 %) were found (p≤0.01), while lower values of NDF (43.08 %), ADF (18.92 %), and high ME (2.57 Mcal·kg-1) were found at 45 d (p≤0.01). The highest ISDMD values were shown at 10 cm of defoliation intensity (p≤0.01), in interaction with 45 d and followed by 30 d of regrowth. It is concluded that a defoliation intensity of 10 cm with maturity stage of 45 d optimizes utilization of Mavuno grass hybrid by ruminants in dry season in the southern region of Jalisco.